2022
DOI: 10.48550/arxiv.2207.10638
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Astrophysical Tests of Dark Matter Self-Interactions

Abstract: Self-interacting dark matter (SIDM) arises generically in scenarios for physics beyond the Standard Model that have dark sectors with light mediators or strong dynamics. The selfinteractions allow energy and momentum transport through halos, altering their structure and dynamics relative to those produced by collisionless dark matter. SIDM models provide a promising way to explain the diversity of galactic rotation curves, and they form a predictive and versatile framework for interpreting astrophysical phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 595 publications
0
18
0
Order By: Relevance
“…The self-interactions can thermalize the inner regions of dark matter halos and affect the distribution of dark matter in galaxies. Recent studies have shown that such a scenario can be favored in explaining kinematic measurements of stars and gas particles in dwarf galaxies, see [125,126]. The advantage of considering inelastic self-interacting dark matter is that it can evade stringent direct detection constraints [127,128] if the mass splitting between χ 1 and χ 2 is sufficiently large such that χ 1 + ξ → χ 2 + ξ is forbidden.…”
Section: Constraining Inelastic Dark Matter With a Light Mediatormentioning
confidence: 99%
“…The self-interactions can thermalize the inner regions of dark matter halos and affect the distribution of dark matter in galaxies. Recent studies have shown that such a scenario can be favored in explaining kinematic measurements of stars and gas particles in dwarf galaxies, see [125,126]. The advantage of considering inelastic self-interacting dark matter is that it can evade stringent direct detection constraints [127,128] if the mass splitting between χ 1 and χ 2 is sufficiently large such that χ 1 + ξ → χ 2 + ξ is forbidden.…”
Section: Constraining Inelastic Dark Matter With a Light Mediatormentioning
confidence: 99%
“…Given the differences we find in the LMC's DM and stellar wakes between FDM and CDM, it is also worth asking whether other DM particle candidates might also impact the DM and/or stellar wake in unique ways. In particular, self-interacting DM (SIDM; Carlson et al 1992;Spergel & Steinhardt 2000; see also Tulin &Yu 2018 andAdhikari et al 2022 for recent reviews), in which the DM particle has some nonnegligible cross section for self-scattering, has emerged as another promising alternative to CDM. In the context of DF wakes, self-scattering between DM particles could potentially alter both the density and velocity of DM particles within the wake, as well as induce a bow shock or mach cone in the DM (Furlanetto & Loeb 2002).…”
Section: Self-interacting Dark Mattermentioning
confidence: 99%
“…The first 𝑁-body simulation using a Monte Carlo scheme of this core formation has been performed by Burkert (2000). Since then SIDM has been found to be capable of solving or at least mitigating further small-scale problems of Cold Dark Matter (CDM) (for a review see Tulin & Yu 2018;Adhikari et al 2022). This does not only include the core-cusp problem (e.g.…”
Section: Introductionmentioning
confidence: 99%